Influence of statin use on prognosis of patients with renal cell cancer: a meta-analysis - Liang, Wenli; Pan, Yongmei; Liu, Aixue; He, Yan; Zhu, Yan (Frontiers in Oncology, 2023)
Background: Statin may confer anticancer efficacy, while the studies evaluating the influence of statin on survival of patients with renal cell cancer (RCC) yielded inconsistent results. A systematic review and meta-analysis was performed to investigate the association between statin use and survival of patients with RCC. Materials and Methods: Cohort studies were identified by search of PubMed, Embase, and Web of Science databases according to the objective of the meta-analysis. A random-effect model incorporating the possible between-study heterogeneity was used for meta-analysis. Subgroup analyses according to study characteristics were also performed. Results: Seventeen cohort studies involving 42528 patients with RCC were available for the meta-analysis. Results showed that statin use was associated with a better overall survival (OS, hazard ratio [HR]: 0.73, 95% confidence interval [CI]: 0.65 to 0.84, p < 0.001; I2 = 40%), progression progression-free survival (PFS, HR: 0.82, 95% CI: 0.68 to 0.98, p = 0.03; I2 = 52%), and cancer-specific survival (CSS, HR: 0.76, 95% CI: 0.59 to 0.99, p = 0.04; I2 = 38%). Besides, for the outcome of OS and PFS, subgroup analyses showed similar results in patients with surgical and non-surgical anticancer treatments, and in patients with stage I-III and stage IV RCC (p values for subgroup difference all > 0.05). Conclusions: Statin use may be associated with improved survival outcomes in patients with RCC. Although prospective clinical studies should be considered to validate these results, these findings suggest that statins may be potential adjuvant therapy for patients with RCC.